To determine which equation Hill is solving where his second step is to divide both sides by 5, we need to consider what that implies for the original equation.
-
7 − 5x = 22:
- If we isolate the term with x, we get \( 7 - 22 = 5x \) which gives \( -15 = 5x \). Dividing both sides by 5 yields \( -3 = x \).
-
7 − x/5 = 22:
- If we isolate x, we rearrange this to \( 7 - 22 = x/5 \) giving \( -15 = x/5 \). Dividing both sides by 5 would not logically follow since we would divide by 5 to get \( x = -75 \).
-
7 + x/5 = 22:
- Rearranging gives \( 7 - 22 = -x/5 \) or \( -15 = -x/5 \) which can be rewritten as \( 15 = x/5\). When we divide by 5, we would find \( 75 = x\).
-
7 + 5x = 22:
- Rearranging gives \( 5x = 22 - 7 \) which results in \( 5x = 15\). When we divide both sides by 5, we get \( x = 3\).
Based on this reasoning, the equation that Hill is solving where dividing by 5 is a logical step after an initial operation (like isolating terms) is:
7 − 5x = 22.